Use of detonation sputtering to increase the durability of hydraulic hammer critical parts - Hlushkova, D.B.; Kyrychenko, I.H.; Bahrov, V.A.; Kalinina, N.Ye.; Nosova, T.V. (Вопросы атомной науки и техники, 2021)
Currently, the use of new methods of surface strengthening has become relevant to improve the working tool. These methods include detonation sputtering. The purpose of this work was to scientifically substantiate and experimentally confirm the effectiveness of strengthening critical parts of a hydraulic hammer by detonation sputtering. As a result of the study, the effect of detonation sputtering on the wear resistance and mechanical properties of the hydraulic hammer working tool was established, and structural changes in the material during its operation were analyzed. The results of testing parts strengthened with detonation sputtering show that an increase in wear resistance by 1.8 times is achieved compared to the initial state. На даний час для підвищення довговічності робочого інструмента стало актуальним застосування нових методів поверхневого зміцнення. До таких методів відноситься детонаційне напилення. Мета даної роботи – науково обґрунтувати і експериментально підтвердити ефективність зміцнення відповідальних деталей гідромолота методом детонаційного напилення. В результаті проведеного дослідження встановлено вплив детонаційного напилення на зносостійкість і механічні властивості робочого інструмента гідромолота, проведено аналіз структурних змін у матеріалі у процесі його експлуатації. Результати випробування деталей, зміцнених детонаційним напиленням, показують, що досягається підвищення зносостійкості в 1,8 рази у порівнянні з вихідним варіантом. В настоящее время для повышения долговечности рабочего инструмента стало актуальным применение новых методов поверхностного упрочнения. К таким методам относится детонационное напыление. Цель данной работы – научно обосновать и экспериментально подтвердить эффективность укрепления ответственных деталей гидромолота методом детонационного напыления. В результате проведенного исследования установлено влияние детонационного напыления на износостойкость и механические свойства рабочего инструмента гидромолота, проведен анализ структурных изменений в материале в процессе его эксплуатации. Результаты испытания деталей, упрочненных детонационным напылением, показывают, что достигается повышение износостойкости в 1,8 раза по сравнению с исходным вариантом.